2021
DOI: 10.1108/tqm-10-2020-0249
|View full text |Cite
|
Sign up to set email alerts
|

Value-based lean implementation in a surgical unit: the impact of the methodology

Abstract: PurposeThis paper aims to present a method for strategic planning and implementation processes in health care based on lean management.Design/methodology/approachWithin the framework of the action research methodology, the authors present the ten steps of a kaizen project, which enable lean transformation over a period of time. The study is underpinned by a literature review of enablers and barriers and an implementation case in a tertiary care hospital.FindingsKey points and possible contingency issues are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Following the principles of the Lean philosophy [47,48] and using action research methodology [18], this section presents a scientific methodology as shown in Figure 1 below that allows the redesign of processes and that can be replicated with the same purpose in other health centers in order to improve patient care. Previous research similar to this paper [18] suggests that there are not many references in the health care field to the action research approach [49][50][51]; it is a sector more focused on case studies.…”
Section: Materials and Methods: Model For The Implementation Of Process Improvement In A Healthcare Environmentmentioning
confidence: 60%
See 1 more Smart Citation
“…Following the principles of the Lean philosophy [47,48] and using action research methodology [18], this section presents a scientific methodology as shown in Figure 1 below that allows the redesign of processes and that can be replicated with the same purpose in other health centers in order to improve patient care. Previous research similar to this paper [18] suggests that there are not many references in the health care field to the action research approach [49][50][51]; it is a sector more focused on case studies.…”
Section: Materials and Methods: Model For The Implementation Of Process Improvement In A Healthcare Environmentmentioning
confidence: 60%
“…The main disadvantage is that it assumes that each process takes a long time to complete, which is not always the case. The main purpose of using action research is to seek the participation and involvement of the researcher as an agent of change along with the other members of the organization because, in the health sector, managing change requires the participation of the entire team involved in the processes identified for improvement [49]. This will allow the knowledge acquired to have a cyclical effect, which in turn will allow further improvement and sharing of that improvement with other organizations and researchers [18].…”
mentioning
confidence: 99%
“…Today, the service industry, especially the hospitals have been wise to adapt to Lean transformation by applying similar Lean techniques to their processes (Yu et al , 2021; Ahn et al , 2021). Lean is an approach which improves healthcare service quality by eliminating faults and decreasing patient waiting times through effective use of available resources (Graban, 2011; Godley and Jenkins, 2019; Sales and De Castro, 2021). Many authors have implemented Lean applications in healthcare through case studies confirming the validity of the methodology (Chiarini, 2014; Jorma et al , 2016; Yurtkuran et al , 2017; Sánchez et al , 2018; Bharsakade et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Tem sido usado com sucesso em diferentes aplicações de saúde, desde pequenas clínicas médicas (Lummus et al, 2006;Rocha & Vasconcelos, 2021) até sistemas mais complexos, como departamentos de emergência, unidades cirúrgicas (Sales & De Castro, 2021). No entanto, os profissionais devem estar cientes de algumas distinções importantes entre manufatura e saúde ao aplicar MFV (Doğan & Unutulmaz, 2016).…”
Section: Mapeamento Do Fluxo De Valor (Mfv)unclassified